THE DEFINITION OF BUSINESS ENTERPRISE OVERVIEW OF LEGAL AND ECONOMIC APPROACHES - Jinoria, Khatuna (European Scientific Journal, ESJ, 2014)
The importance of establishing common legal definition of business enterprise is not merely a subject of legal theory. It raises the problem of the legal theory enterprise or, simply, who is the subject of corporate law, enterprise, entrepreneur or the society (company)?! A unified approach or common definition of business enterprise is not established. In general, legal writers agree on the basic, general outlines, but the diversity begins with every suggestion of more presition. The purpose of this article is to overview all the approaches to the concept of enterprise, discuss legislative and economic suggestions in this field and, in the end, to offer a unified definition of the enterprise.